776 Patient Outcomes Vary with Surgeons' Experience Following Emergency Laparotomy: An Observational Study. (19th August 2022) - Sultana, E; Naumann, DN; Williamson, A; Griffiths, E; Bedford, M; Karandikar, S
Abstract: Aim: There is some evidence that patient outcomes for surgeons improve with years of experience. We aimed to investigate the relationship between surgeon experience and patient outcomes following an emergency laparotomy in a large sample of the UK National Emergency Laparotomy Audit (NELA) database. Method: A 5-year retrospective observational study was undertaken using data extracted from NELA for patients who underwent emergency laparotomies at a large UK multi-site NHS Trust. The association between 30-day mortality and surgeon years of experience was investigated using logistic regression, adjusted for ASA grade, patient age and gender, Index of Multiple Deprivation (IMD) score, and time of surgery. Results: There were 3153 patients with a median age of 66 (IQR 51–76), and 49.4% were male. Patients in the group who died within 30 days were more likely to be older, have a higher ASA score, and have an operation during the night. Increasing years of surgeon experience, patient age, and ASA were all significantly associated with increased odds ratio of death within 30-days. Conclusions: Increasing years of surgical experience appears to be related to worse patient outcomes for an emergency laparotomy. This is likely due to surgeons taking on more complex and challenging cases as their career progresses. Further explorations of how surgeons' activity changes over their full career are warranted.